CESTODES OF THE FLOUNDER PARALICHTHYS ISOSCELES JORDAN, 1890 (OSTEICHTHYES - PARALICHTHYIDAE) FROM THE STATE OF RIO DE JANEIRO, BRAZIL - Nunes Felizardo, Nilza (2010)
From October 2006 to March 2008, sixty specimens of Paralichthys isosceles, were captured in the littoral of the State of Rio de Janeiro Brazil. The present study deals with the taxonomic identification of the cestodes parasitizing this fish species, as well with the analysis of parasitological indexes, sites of infection, taking into account the hygienic-sanitary importance of the host in Brazilian and foreign markets. Fifty-six (93.3%) out of the collected fishes were infected with at least one specimen of metacestodes. Diphyllobothriidea were represented by plerocercoids of two species: Diphyllobothrium sp. 1 (similar to D. latum) in stomach, stomach mucosa and mesentery and Diphyllobothrium sp. 2 (similar to D. dendriticum) in intestine, liver, ovary and abdominal cavity. Trypanorhyncha, were represented by Grillotia carvajalregorum, in stomach, intestine, liver, mesentery, abdominal cavity, abdominal and dorsal musculatures, Nybelinia lingualis in stomach, stomach mucosa, intestine, mesentery, spleen serosa, dorsal musculature, Heteronybelinia nipponica in intestine, kidney serosa, abdominal cavity and abdominal musculature, Otobothrium sp. in the stomach, intestine, liver, mesentery and abdominal cavity, Callitetrarhynchus gracilis and Pterobothrium heteracanthum in abdominal musculature, P. crassicolle in stomach serosa. Tetraphyllidea, were represented by Scolex pleuronectis in stomach and intestine. Remarks on the zoonotic potential of species included in Diphyllobothriidae and Trypanorhyncha and the role they play concerning sanitary inspections are presented. This is the first report of metacestodes parasitizing specimens of P. isosceles.